Rural Resilience and Voluntary Work in the North of Sweden: An Ambiguous Relationship - Nilsson, Bo (Journal of Northern Studies, 2021)
Rural areas in the north of Sweden are characterized by depopulation, unemployment and undermined social services. Due to the demands of economic growth and development, major cities in southern Sweden have been prioritized at the expense of the countryside. However, there have been many reactions to the dismantling of the welfare society in rural areas. People are also trying to counter and compensate for the impoverishment of the countryside through voluntary work. The overarching aim of this paper is to explore meanings of voluntary work in Sweden’s northern county of Västerbotten. More specifically, the aim is to investigate how different comprehensions of rural voluntary work are related to rural identities and to a resilient rural society. A central argument in the paper is that the relation between rural volunteer work and rural resilience is ambiguous. On one hand, volunteer work can contribute to rural resilience, since volunteering is a necessary course of action for people in the countryside to secure a necessary level of social services. On the other hand, rural volunteer work often has a traditional character, not always representing the capital of knowledge needed to maintain a sustainable rural lifestyle in the long run.